Landslide Disaster Mitigation Education in Creating Disaster-Responsive Villages - Yeni Nur Rahmayanti; Eka Novitayanti; Fadma Aji Pramudita; Pipi Anonyma (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: Indonesia is prone to natural disasters such as earthquakes, volcanic eruptions, tsunamis, floods, and landslides. Landslides are the movement of masses of soil or rock from slopes, usually caused by heavy rainfall, earthquakes, or human activity. Jenawi District has varied topography, ranging from hills to mountainous areas. This place has a variety of heights, ranging from slopes to very steep areas. This area also has slopes ranging from 15-30% and high annual rainfall.Aims: To increase knowledge of landslide disaster mitigation. The population for this community service program is residents of Jenawi Village.Method: Focus Group Discussion (FGD) was used. The population consisted of 55 men and women from Jenawi Village. Jenawi District has many steep slopes and receives significant rainfall. This situation results in widespread erosion, soil decomposition, and landslides. Based on this identification, Mitra Husada Karanganyar Health College aims to educate residents about landslides and disaster-responsive villages.Results: The community service activities ran smoothly, and understanding of landslides and disaster response increased by 76,4%.Conclusion: Community knowledge about landslide mitigation has increased, but true knowledge is inseparable from education.